2015
DOI: 10.1515/pjvs-2015-0100
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pentatrichomonas hominis in dogs using real-time PCR

Abstract: Trichomonadidae family is a protozoan occurring in different animal species. It inhabits the gastrointestinal and urinary tracts. P. hominis is rarely found in faecal samples of dogs, and its identification and differentiation from other trichomonads by light microscopy are difficult. Methods of molecular biology are the most effective in this case, because they confirm the presence of the specific species in animal organisms, irrespective of the protozoan form. The aim of this study was to find P. hominis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
1
5
1
Order By: Relevance
“…Based on our molecular detection and sequencing results, the several isolates obtained from cats, dogs and cattle were confirmed to be P. hominis- positive. These findings implied that cats, dogs and cattle could act as natural hosts of P. hominis , which are consistent with the results of previous studies [ 2 , 5 , 24 , 27 ]. P. hominis may be a potential organism for zoonotic transmission in people who are in close contact with infected animals or consume water contaminated with P. hominis [ 5 , 7 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Based on our molecular detection and sequencing results, the several isolates obtained from cats, dogs and cattle were confirmed to be P. hominis- positive. These findings implied that cats, dogs and cattle could act as natural hosts of P. hominis , which are consistent with the results of previous studies [ 2 , 5 , 24 , 27 ]. P. hominis may be a potential organism for zoonotic transmission in people who are in close contact with infected animals or consume water contaminated with P. hominis [ 5 , 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the natural behaviour of grooming among cats supports the transmission of infection through physical contamination [ 11 , 24 ]. The prevalence of P. hominis in dogs in this study was lower than those reported in China, Japan, South Korea and Poland [ 8 , 24 , 26 , 27 ]. However, similar to previous reports, P. hominis infections were dominant in cats and dogs in the present study [ 19 , 22 , 24 , 31 ].…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…However, there are several reports that represent the status in pet shop animals. The recent molecular prevalence of P. hominis from young dogs has been recorded as follows: 17.4% (19/109; breeding kennel dogs aged <8 weeks) in France (Grellet et al, 2013), 41.5% (49/118; police dogs and rural district dogs aged ≤6 months) in China (Li et al, 2016b), 12.5% (4/32; breeding kennel dogs aged ≤6 months) in Poland (Michalczyk et al, 2015) and 53.3% (24/45; household dogs aged ≤12 months) in China (Li et al, 2016a). In young cats, the following molecular prevalence of T. foetus was lately described: 26.3% (5/19; show cats aged <12 months) in Norway (Tysnes et al, 2011), 11.7% (7/60; household cats aged ≤12 months) in China (Li et al, 2019) and 33.3% (12/36; household cats aged ≤12 months) in Poland (Dąbrowska et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Especially, in humans under the suppressive immune system (e.g., children and adult patients with cancer), P. hominis has been implicated as a causative agent of diarrhea (Meloni et al, 2011;Zhang et al, 2019). In dogs and cats, the coinfection of other protozoa with P. hominis is also presumed to increase the incidence of diarrhea (Grellet et al, 2013;Michalczyk et al, 2015). As to protozoan T. foetus, the pathogenicity has not been demonstrated in dogs (Li et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%